2006
DOI: 10.1158/0008-5472.can-05-4253
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal Anti-inflammatory Drugs and the Esophageal Inflammation-Metaplasia-Adenocarcinoma Sequence

Abstract: Observational studies suggest that nonsteroidal anti-inflammatory drugs (NSAIDs) reduce the risk of esophageal adenocarcinoma, but it is not known at what stage they may act in the esophageal inflammation-metaplasia-adenocarcinoma sequence. In an all-Ireland case-control study, we investigated the relationship between the use of NSAIDs and risk of reflux esophagitis, Barrett's esophagus, and esophageal adenocarcinoma. Patients with esophageal adenocarcinoma, long-segment Barrett's esophagus and population cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
4
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(116 citation statements)
references
References 48 publications
(57 reference statements)
3
108
4
1
Order By: Relevance
“…Infection with Helicobacter pylori, Barrett's esophagus, hiatal hernia, and reflux symptoms are independent risk factors for esophageal and gastric adenocarcinomas in this study population (14,23,24). Presence of these and other UGI conditions can influence the use of NSAIDs (39); in fact, for several of these conditions, NSAID use is contraindicated.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Infection with Helicobacter pylori, Barrett's esophagus, hiatal hernia, and reflux symptoms are independent risk factors for esophageal and gastric adenocarcinomas in this study population (14,23,24). Presence of these and other UGI conditions can influence the use of NSAIDs (39); in fact, for several of these conditions, NSAID use is contraindicated.…”
Section: Discussionmentioning
confidence: 95%
“…Most previous studies of the relationship between NSAID use and risk of esophageal or gastric cancer have defined the reference group as individuals whose NSAID use history falls below a certain threshold (14,15,20,21,38,41,42), similar to our approach where the reference group consisted of individuals whose had never used at least two NSAID pills per week for 1 month. Two studies have separated irregular users from never users (22,37), but neither separated adenocarcinomas of the esophagus from squamous cell carcinomas nor did either study segregate gastric cancers by site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We limited our analysis to papers reporting case -control or cohort studies of the association between the use of either aspirin or non-aspirin NSAIDS and the risk of oesophageal or gastric adenocarcinomas. We included the following studies for the oesophagus (Farrow et al, 1998;Cheng et al, 2000;Lindblad et al, 2005;Anderson et al, 2006;Jayaprakash et al, 2006;Ranka et al, 2006;Fortuny et al, 2007;Duan et al, 2008;Sadeghi et al, 2008), cardia (Farrow et al, 1998;Zaridze et al, 1999;Akre et al, 2001;Fortuny et al, 2007;Duan et al, 2008;Sadeghi et al, 2008), non-cardia (Farrow et al, 1998;Zaridze et al, 1999;Akre et al, 2001;Fortuny et al, 2007;Duan et al, 2008), and gastric NOS (Thun et al, 1993;Schreinemachers and Everson, 1994;Coogan et al, 2000;Langman et al, 2000;Akre et al, 2001;Sorensen et al, 2003;Ratnasinghe et al, 2004;Lindblad et al, 2005) and excluded a few studies from certain sections that did not specify the agent (Garidou et al, 1996;Suleiman et al, 2000) or the histology of the oesophageal tumours (Funkhouser and Sharp, 1995;Langman et al, 2000). Two other studies, one prospective and one retrospective, reported on the association between aspirin and oesophageal adenocarcinoma, but included only subjects with Barrett's oesophagus in the reference group (Tsibouris et al, 2004;Vaughan et al, 2005) and these pap...…”
Section: Meta-analysismentioning
confidence: 99%
“…This response has been also implicated in the initiation and progression of cancer (de Visser and Coussens, 2005;Khan and Tomasi, 2008). For instance, some malignancies may be prevented by the use of anti-inflammatory drugs (Anderson et al, 2006;Rigas, 2007). Inhibition of certain proinflammatory cytokines has also been shown to decrease the aggressiveness of some tumor types Abbreviations: GM-CSF, granulocyte-macrophage colony-stimulating factor; HDAC, histone deacetylase; IFN, interferon; IL, interleukin; NF-kB, nuclear factor-kB.…”
Section: Hdacs and Regulation Of Proinflammatory Cytokinesmentioning
confidence: 99%